FROM TRAUMA TO POSTTRAUMATIC STRESS DISORDER (Annual of the Faculty of Philosophy in Skopje, 2009)
This review describes the history of the concept of posttraumatic stress disorder, from the earliest available historical writings, thru the multitude of terms used to define the posttraumatic response especially duung World War I and II , up to the birth of this diagnostic category in 1980. The modifications of the definition of posttraumatic stress disorder in the past two decades are also discussed, as well as the critiques and limitations of the concept.
Keywords: TRAUMA; POSTTRAUMATIC STRESS DISORDER; PTSD